2013
DOI: 10.1177/0148607112471560
|View full text |Cite
|
Sign up to set email alerts
|

Osmolality, pH, and Compatibility of Selected Oral Liquid Medications With an Enteral Nutrition Product

Abstract: When selecting medication for feeding tube administration, the liquid formulation is selected, so as to avoid obstructions that may occur from incompletely crushing a solid dosage form. Liquid medications can present issues of intolerance and compatibility when administered via a feeding tube. A predictor of intolerance is the liquid's osmolarity, and a predicator of compatibility is the liquid's pH value. This study examines 62 liquid formulations for their osmolality, pH, and physical compatibility with ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 18 publications
0
46
0
2
Order By: Relevance
“…The midazolam solubility profile, including its significant drop from 2.4 mg/ml at pH 4.2 to 0.4 mg/ml at pH 5.0, has been previously reported [33]. At physiologic conditions (pH [5][6][7][8], any openring form present reverts to the physiologically active, lipophilic, closed-ring form of midazolam, and is absorbed into the systemic circulation as such [39]. With the rationale for midazolam acidic syrup formulation understood, it was concluded that there was no specific concern for including midazolam in the 8-drug cocktail based on 2 considerations: 1) The inclusion of midazolam acidified the drug cocktail mixture, however, the other drugs were all designed to first encounter an acidic environment in a human stomach anyway and therefore the impact should be minimal.…”
Section: Excipients Physicochemical Properties and Formulation Desigmentioning
confidence: 89%
See 1 more Smart Citation
“…The midazolam solubility profile, including its significant drop from 2.4 mg/ml at pH 4.2 to 0.4 mg/ml at pH 5.0, has been previously reported [33]. At physiologic conditions (pH [5][6][7][8], any openring form present reverts to the physiologically active, lipophilic, closed-ring form of midazolam, and is absorbed into the systemic circulation as such [39]. With the rationale for midazolam acidic syrup formulation understood, it was concluded that there was no specific concern for including midazolam in the 8-drug cocktail based on 2 considerations: 1) The inclusion of midazolam acidified the drug cocktail mixture, however, the other drugs were all designed to first encounter an acidic environment in a human stomach anyway and therefore the impact should be minimal.…”
Section: Excipients Physicochemical Properties and Formulation Desigmentioning
confidence: 89%
“…For example, the stability of commonly used drugs with enteral nutrient formulas (ENFs) was studied to ensure the suitability of using these drugs for patients on ENFs. The reported methods for determining the physical compatibility of drugs with ENFs include the observation/determination of viscosity change, particle growth, granulation, precipitation, phase separation, pH and osmolarity change, and concentration analysis [4][5][6][7][8][9]. It has reported that some drugs formed a solid mass immediately in the test tube with ENF [5], this reaction could have caused the obstruction of a feeding tube.…”
Section: Introductionmentioning
confidence: 99%
“…When pH is lower than 3.5 it may interfere in gastric motility and contribute towards a slower gastric emptying (Araújo & Menezes, 2006;Klang et al, 2013;Blumenstein et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Its analysis is important to assess the physiological acceptance capability of the diet and to avoid complications (Barrett et al, 2009 by providing a solubility environment to the nutrients. It is also crucial for the microbiological control of the solution (Klang et al, 2013;Pinto et al, 2015). Non-industrialized enteral diets with a pH rate favorable to microbiological growth may be an infection vector for patients undergoing enteral nutritional therapy if preventive hygiene measures are not applied during food handling (Blumenstein et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Osmolality is a crucial determinant of the physiological acceptance of the beverage. The desired osmolality should be < 700 mOsm (Klang, McLymont, & Ng, 2013). An appropriate osmolar load is necessary for the beverage be tolerated by a eutrophic elderly consumer, ensuring the successful assimilation of the formulation components.…”
Section: Osmolalitymentioning
confidence: 99%